DEVELOPMENT OF INDUSTRY AND ECONOMY IN SURKHANDARYA DURING THE YEARS OF INDEPENDENCE - Bohodir Saidmusaevich Rakhimov (Scholar Express Journal, 2021)
This article analyzes the effect of reforms implemented during the years of independence in the development of the economy and industry in Surkhandarya region. The issues of the positive impact of the economic development of the southern oases on the living standards of the population were also discussed.
Keywords: Economic Development; Industry; New Modernization; Spinning Mill